Analisis kemampuan guru dalam penggunaan perangkat chromebook pada pembelajaran IPAS di kelas V sekolah dasar - Eska Asanti; Siti Istiyati; Fadhil Purnama Adi (Universitas Sebelas Maret, 2024)
The aim of this research is to describe teachers' abilities in using chromebook media in science and social studies learning in class V of SD Negeri Cinderejo, Surakarta city. This research is qualitative descriptive research with a case study approach. The research subject was a fifth grade teacher at Cinderejo State Elementary School, Surakarta City. The data collection techniques used were written tests, observations, interviews. and documentation. Content validity is carried out by expert assessment. Data validity uses source triangulation and technical triangulation. The data analysis used is the interactive analysis of the Miles and Huberman model. The research results show that the ability of class V teachers to use chromebook media is theoretically in the